STRATEGI REVITALISASI KAWASAN WISATA SANGEH (STUDI KASUS DENGAN PENDEKATAN ANALISIS SWOT) - I Wayan Edi Arsawan; Ni Made Kariati; I Wayan Wirga; Ni Putu Santi Suryantini (Soshum: Jurnal Sosial dan Humaniora, 2016)
This study investigates and finds the composition strategy of revitalizing Sangeh tourism destination most feasible to examine various factors internal and external to provide alternative management assisted with a touch of modern management and utilization of information technology relevant to stick to local wisdom (local genius) so that the various potentials Sangeh region can be managed with more organized, structured, accountable and secure its sustainability so that their indirect impact is the increased standard of living of the surrounding communities and the sharpening of the various potential areas and human resources. The method used in this research is descriptive method qualitative with direct conduct field observations, interviews with the manager, prajuru (figure) village and visitors Sangeh tourism destination so on get a composition data from two directions managers (stakeholder) and visitors (tourists ) to formulate policies / strategies are most worthy to revitalize Sangeh tourism destination. From the results of SWOT analysis results of the most dominant options strategy is a strategy SO (strength Opportunities); strategies utilize all the power and take advantage of opportunities as possible for that; 1) the maintenance and development of road access 2) an increase in promotion and travel packages with proper media selection, 3) more often hold events / festivals to increase the number of 4) increase of supporting facilities such as accommodation, restaurant and souvenir shop sellers. From interviews and questionnaires to tourists the average respondent to respond positively and constructively while still giving emphasis on improving access to transport, inadequate infrastructure and lack of clean and lack of information about Sangeh in the new location.